Музичките состави од инструменталната македонска етнопоп музика од 80-тите години на 20-тиот век - Димитријевски, Александар (Асоциация за антропология, етнология и фолклористика „Онгъл“, 2021)
The instrumental Macedonian ethnopop music was the main subject of interest in one of my previous researches dedicated to its most profound development especially in the 1980ties. In this paper the primary focus is set to the instrumental ensembles which characterize this music as a unique music phenomenon and its musical pieces as its primary product. The conclusions are based on the analysis of the music characteristics of the recorded material which forms the database of the sample of 100 music pieces (generated from a large population of 610 pieces). Also, a special attention is dedicated to the creativity, in other words to the process of creation of the instrumental Macedonian ethnopop music versus the reproductive process of this music.
The music ensembles of the instrumental Macedonian ethnopop music from the 1980ties
Тринадесети Цар- Шишманови дни в Самоков на Асоциация за антропология, етнология и фолклористика „Онгъл“
Keywords: Macedonian music folklore, Macedonian ethnopop music, 1980ties